Analysis Of the Roles of Artificial Intelligence in News Programme Production at Select Commercial Radio Stations in Southwest Nigeria - Oko-Epelle , Lydia; Oyedeji, Azeem Alade; Olanrewaju, Maranatha Morenike; Ezeakolam, Amarachi Agatha; Shodipe Oluwafunmilayo (Corpus Intellectual, 2024)
The evolution of artificial intelligence (AI) is increasingly impacting various aspects of society, including the media. To remain relevant, commercial radio stations must adapt to these technological advancements. This study explores the role of AI in news production at select commercial radio stations in Southwest Nigeria. The objectives include assessing the level of AI awareness, identifying specific roles of AI, and understanding the challenges of integrating AI into broadcast production among these stations. The study is grounded in Diffusion of Innovation Theory and the concept of Metamorphosis. A survey design was employed, using a questionnaire to collect data from 122 registered members of the Association of Nigerian Radio Broadcasters. The findings reveal that most of the selected commercial radio stations in Southwest Nigeria are aware of AI's presence in media production. Key roles identified for AI include audio editing and enhancement, transcription of text to audio, voiceovers, program summarisation, automated announcements, and news script generation. The challenges encountered include staff inexperience and concerns about the authenticity and ethical implications of AI-generated content. The study concludes that automation represents the future of media, and commercial radio stations must embrace this shift to remain competitive on a global scale.